Ultrafast all-optical tuning of magnetic modes in GaAs metasurfaces - Shcherbakov, Maxim R.; Liu, Sheng; Zubyuk, Varvara V.; Vaskin, Aleksandr; Vabishchevich, Polina P.; Keeler, Gordon; Pertsch, Thomas; Dolgova, Tatyana V.; Staude, Isabelle; Brener, Igal; Fedyanin, Andrey A. (2017 Conference on Lasers and Electro-Optics, CLEO 2017 - Proceedings, 2017)
We experimentally realize an ultrafast tunable metasurface consisting of subwave-length gallium arsenide nanoparticles supporting Mie-type resonances, which are all-optically tuned by 30 nm in spectral domain under pump fluences as low as < 400 µJ/cm2.
CRIS-Team Scopus Importer:2023-04-20